Dynamic Capital Structure and Its Speed of Adjustment: A Case of Listed Manufacturing Firms in Indonesia - Anisti, Novia Putri; Chalid, Dony Abdul (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aims to examine the dynamic aspects in the capital structure decisions of manufacturing firms in Indonesia, offering a continuation to the existing literature on Indonesia by using a dynamic model, including the existence of optimal capital structure, the determining factors, the speed of adjustments, and the aiding theories to explain the findings. The findings show that Indonesian manufacturing firms do practice optimal capital structure and are altered by firm-specific and time-varying factors. Despite relatively recent data and more specific sample firms (one industry only), the results of this study still need to be further developed. The sample chosen focused on listed firms, hence the results may not be generalized to all Indonesian manufacturing firms. This research is expected to have profound implications for future studies of capital structure and might one day be able to help firms, investors, and authorities in making effective decisions, as well as analysts in observing the correlation between the capital structure theories and the financing practice of manufacturing firms in Indonesia.